RIGHTS OF THE MECHANISMS OF THE STATE MANAGEMENT FOR THE DEVELOPMENT OF THE DEVELOPMENT OF FOREIGN DEVELOPMENT IN UKRAINE - HRUSHETSKYI, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the legal mechanisms for the development of higher education in Ukraine. The management of the lighting sphere of Ukraine has been reviewed in terms of the legal aspect. Vіdnosin in the sphere of social development. The main legislative acts, which are observed in the field of higher education of Ukraine at the legislative and regional level, have been designated. The main legislative act is the Constitution of Ukraine, Article 53, which secures the right of the skin to the illumination. The act on the adoption of the pledge is the Law of Ukraine No. 1060-XII "On the Light" dated 23 January 1991, which establishes the forward and basic norms of legal regulation in the field of higher education. Chinna edition of the law was passed on December 18, 2019. Other relevant laws establish and supplement their regulatory provisions, for example, the Law of Ukraine “On the Protection of the Light of Ukraine” dated 16.09.2022. No. 1556-VII. The main mutual tendencies of the current legal regulation of the system of higher education are characterized: the need to adopt a new Law “On the Protection of Light”, or to introduce substantive changes to the future; renewing the criteria for evaluating the validity of the Ukrainian primary foundations, which in turn meet the light standards of the quality of illumination; promoting the development of scientific talents, and itself assigning scientific degrees to doctors and candidates of sciences.